Optimization of biodegradation efficacy of acrylic-based paint contaminated soil by Alcaligenes faecalis - P. I. Orjiakor (Novel Research in Microbiology Journal)
Acrylates/acrylic-containing chemicals are components of paints. During industrial production and applications, the acrylates and acrylic-containing compounds could contaminate/accumulate in water bodies and soil systems, hence the need for bioremediation. This study aimed to investigate the in vitro biodegradation of acrylic based paint; using an indigenous bacterial isolate namely; Alcaligenes faecalis and optimization of its activity in shake cultures. The bacterial isolate; A. faecalis (2 % v/v) was able to grow and effectively degrade 68 % of acrylic paints (1 %)-mended mineral salt medium after 14 d of incubation. The rate of biodegradation was significantly (p< 0.05) increased with increasing the medium concentration, inoculum size, agitation speed and nitrogen sources. The most significant biodegradation efficiencies were obtained at a pH of 7.2, temperature of 37 °C, an agitation speed of 200 rpm, an inoculum concentration of 10 %, paint concentration of 2 %; when yeast extract (10 %) was used as a major nitrogen source. Accordingly, this work provides baseline data for optimum biodegradation of acrylate by A. faecalis, and thus could be possibly exploited as an effective bioremediation agent for acrylic paint polluted sites.